Effects of ski stiffness in a sequence of ski turns - Mössner, M.; Heinrich, D.; Kaps, P.; Schretter, H.; Nachbauer, W. (Science and Skiing IV, 2009)
INTRODUCTION: The performance of ski turns mainly depends on skier actions, material properties, snow conditions, and speed of the skier. In this work we focus on effects due to ski material properties among which bending and torsional stiffness are important ones.